COMPREHENSIVE MARKETING IN THE STRUCTURE OF ENTERPRISE MANAGEMENT - TSIKHANOVSKA, Olena; SYSOIEVA, Inna (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the role and functions of marketing in the conditions of modern business. It is shown that marketing is an indispensable tool for influencing consumer behavior aimed at stimulating the sale of products, while its implementation depends entirely on the activities of the enterprise itself.     The main role and functions of marketing activity and their impact on increasing the efficiency of the enterprise's functioning are determined.Special attention is paid to the study of the importance of marketing in the management of manufacturing enterprises. It is considered as one of the key functions of management and a management concept that plays a decisive role in ensuring the stable operation of the organization. Innovative approaches to the improvement of marketing activity are proposed, which can find practical application in the activities of enterprises. The recommendations are aimed at increasing the effectiveness of marketing strategies and improving the overall management of the enterprise.The article explores the role of comprehensive marketing in enterprise management, .particularly its impact on strategic planning, adaptation to a dynamic market environment, and ensuring competitiveness. It examines the integration of digital technologies, ecological initiatives, and innovations into marketing activities to build sustainable competitive advantages. The prospects for further research are outlined, focusing on the use of marketing tools for the long-term development of enterprises.
Keywords: marketing; market research; marketing activity; marketing strategies; costs; demand; competition; advertising; comprehensive marketing